'We have the time to listen': community Health Trainers, identity work and boundaries. Issue 4 (7th August 2020) - Allen-Collinson, Jacquelyn; Williams, Rachel; Middleton, Geoff; Henderson, Hannah; Crust, Lee; Evans, Adam
ABSTRACT: This article contributes empirical findings and sociological theoretical perspectives to discussions of the role of community lay health workers, including in improving the health of individuals and communities. We focus on the role of the Health Trainer (HT), at its inception described as one of the most innovative developments in UK Public Health policy. As lay health workers, HTs are tasked with reducing health inequalities in disadvantaged communities by supporting clients to engage in healthier lifestyles. HTs are currently sociologically under-researched, particularly in relation to occupational identity work, and the boundary work undertaken inter-occupationally with other health workers. To address this research lacuna, a qualitative study was undertaken with 25 HTs based in the Midlands region of the UK. In theorising our findings, we employ a novel combination of symbolic interactionist conceptualisation of 1) identity work, and of 2) boundary work. The article advances knowledge in the field of health and exercise by investigating and theorising how HTs construct, work at, manage, and communicate about professional/occupational boundaries, in order to provide personalised support to their clients in achieving and sustaining healthy behaviour change within the constraints of clients' lifeworlds.